A Randomized Controlled Trial on the Effect of Music Listening on Procedural Pain, Anxiety and Comfort Levels during Cystoscopy. Issue 4 (21st April 2023) - Durgun, Hanife; Yaman Aktaş, Yeşim
ABSTRACT: This study aimed to determine the effect of music listening on procedural pain intensity, anxiety, and comfort levels in patients during cystoscopy. This study was a prospective, randomized controlled trial. Study participants were randomly assigned to either a control or music group. The outcome measures were assessed using the Visual Analogue Scale, State Anxiety Scale, and General Comfort Questionnaire. A total of 36 patients in each group completed the study. The mean scores of pain in the music and control groups immediately after cystoscopy were 3.22 ( SD, 1.72 ) and 5.22 ( SD, 1.92 ), respectively. A statistically significant difference (between-group effect) was found, indicating that pain scores in the music group were significantly lower than those of the control group ( group: F = 15.756, p < .001 ). However, no statistically significant difference was noted between the two groups regarding anxiety and comfort scores 20 min after cystoscopy ( t1  = 1.156, p = .526; t1  = −0.586, p = .560, respectively ). Music listening is a safe, economical, and effective method in pain management in patients undergoing cystoscopy.